Pengembangan LKPD Berbasis Project Based Learning Pada Tema 4 Berbagai Pekerjaan Kelas IV SD - Novia Ananda Sitepu; Nila Lestari (Departement of Mathematics Education, 2023)
This research is a type of research and development with reference to the 4D model which is an extension of Define, Design, Development and Dissemination. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. The results of the validation of the teacher's response in class IV media did not have revisions, and obtained a percentage of 92%. The results of the validation of the assessment by media experts obtained 96% of the 10 statements. The results of the validation of the assessment by material experts get a score of 94% of 14 statements.